MENINGKATAN KETERAMPILAN LOMPAT JAUH GAYA JONGKOK MELALUI MODIFIKASI ALAT BANTU - Widiastuti Widiastuti; Pramudito Hutumo (Gladi : Jurnal Ilmu Keolahragaan, 2018)
This study attempts to improve learning outcomes the long jump style squat through modification learning tool .Of research in SMAN 1 Kotagajah Lampung .Research methodology used is research methodology the act of (action research) . technic the data such quantitative data and qualitative .This research result of the study results the long jump style squat through a learning modification .Increased is evident from the test rata-rata students , to test = 73.09 early , and then students tests showed a rise in cycle i = 80,84 .To learn students graduation the results of a pretest long jump students who passed a number of 9 students ( 36 % ) , cycles i students who passed a number of 25 students ( 100 % ) instrument tests for research has been tested reliability , with the r = 0,84 .According to Suharsimi Arikunto ( 2006 ) , the r = 0.84 can be said this instrument high reliability.